Preparation method and application of nano calcium silicate hydrate type super early strength agent
By preparing nano-hydrated calcium silicate type ultra-premature strength agent, the dispersion of nanoparticles is enhanced by using lanthanum nitrate and cerium nitrate, and the electrostatic repulsion is enhanced by polyparabenide diamine, the early stage of existing early strength agents on cement-based materials is solved. The problem of limited strength enhancement effect has achieved the effect of significantly improving the early strength of concrete and shortening the settling time.
Patent Information
- Application Number
- CN202310533132.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-12
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2043-05-12
AI Technical Summary
The existing early strength agents have limited effect on the early strength improvement of cement-based materials, especially after the accelerated hydration period, the strength of concrete increases slowly, affecting engineering application.
Using the preparation method of nano-hydrated calcium silicate type ultra-premature strength agent, by adding lanthanum nitrate and cerium nitrate to the polycarboxylic acid water reducing agent solution, and polymerizing polyparabenylenediamine on hydrated calcium silicate in situ. The formation of nano-hydrated calcium silicate particles with small particle size and high dispersion significantly reduces the nucleation barrier of the hydrated product C-S-H gel, increases the nucleation site, and promotes the cement hydration rate.
The early strength of concrete was significantly improved, so that the 1d and 3d strengths of concrete reached the 3d and 7d strengths of blank samples, respectively, promoted the strength growth after the acceleration period of hydration of prefabricated components, accelerated mold release and lifting, and reduced steam maintenance links.
Smart Images

Figure BDA0004225083600000111 
Figure BDA0004225083600000121
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of early strength agents, and in particular to a preparation method and application of a nano calcium silicate hydrate type ultra-early strength agent. Background Art
[0002] Efficient use of cement clinker to prepare low-carbon concrete and products that meet engineering needs is one of the important technical approaches to energy conservation and emission reduction in the cement concrete industry. However, the low early strength of concrete restricts its application in engineering.
[0003] The main technical approaches and mechanisms for obtaining high early strength of cement-based materials are as follows:
[0004] (1) Add inorganic early strength agent and cement C 3 A mineral reacts to form calcium sulfide, which improves the early strength of mortar concrete, or forms mixed crystals with antifreeze at negative temperatures to improve antifreeze properties.
[0005] (2) Adding alkanol organic early strength agents can promote the dissolution of aluminum phase in cement and improve early strength. The disadvantage is that it may lead to a decrease in later strength and flexural strength.
[0006] (3) Accelerate the cement hydration process and volcanic ash reaction through steam curing or autoclaving. This type of technical method is mainly used for the curing of cement products.
[0007] Conventional early strength agents and early strength water reducing agents have limited effects on the strength development of cement-based materials from the hydration acceleration period to 24 hours. In recent years, the ultra-early strength performance of nano-hydrated calcium silicate has received widespread attention from scholars at home and abroad. 3 S hydration site, accelerates the hydration process of cement within 3 days, and can make the 1d and 3d strength of concrete reach the 3d and 7d strength of blank samples respectively, which has a significant effect on improving the early strength of concrete, especially promoting the strength growth of prefabricated components after the accelerated hydration period, accelerating demoulding and lifting, and reducing steam curing links.
[0008] Therefore, the development of nano-calcium silicate hydrate crystal nucleus-type early strength agent will help to efficiently utilize clinker cement, and make concrete and its products have early strength and super early strength properties, which has important application value and practical significance. Summary of the invention
[0009] The object of the present invention is to provide a preparation method and application of a nano calcium silicate hydrate type super early strength agent. The prepared nano calcium silicate hydrate type super early strength agent has a small particle size and strong dispersibility, can effectively reduce the nucleation barrier of the hydration product CSH gel, form more nucleation sites, accelerate the cement hydration rate, and effectively improve the early strength of concrete.
[0010] To achieve the above objectives, the present invention is implemented through the following technical solutions:
[0011] A method for preparing a nano calcium silicate hydrate type super early strength agent comprises the following steps:
[0012] (1) adding a polycarboxylate water-reducing agent / lanthanum nitrate / cerium nitrate aqueous solution to a reactor, and adding a sodium hydroxide solution to adjust the pH value to 11.5-12, heating to 50-55° C., and then dripping a calcium salt aqueous solution and a silicon salt aqueous solution into the reactor while stirring under nitrogen protection, after the dripping is completed, adding a sodium hydroxide solution to adjust the pH value to 12-12.5, closing the reactor and heating to 70-80° C., and continuing to stir the reaction at a constant temperature;
[0013] (2) then cooling to 40-50° C., adding dilute nitric acid solution to adjust the pH value to 7-7.5, and under nitrogen protection, adding p-phenylenediamine aqueous solution and ammonium persulfate aqueous solution to the reaction kettle while stirring. After the addition is completed, the reaction is continued with constant temperature stirring, and then cooled to room temperature, centrifuged and washed, and freeze-dried to obtain the nano-hydrated calcium silicate type super early strength agent.
[0014] Preferably, in step (1), in the polycarboxylate water-reducing agent / lanthanum nitrate / cerium nitrate aqueous solution, the mass fraction of the polycarboxylate water-reducing agent is 3-6%, the mass fraction of the lanthanum nitrate is 0.1-0.2%, and the mass fraction of the cerium nitrate is 0.05-0.15%.
[0015] Preferably, in step (1), the preparation method of the polycarboxylate water-reducing agent comprises the following steps: adding 160-180 parts of isobutylene alcohol polyoxyethylene ether, 15-25 parts of methacrylic polyglycol ether and 150-170 parts of water to a reactor, stirring and heating to 80-85° C. under nitrogen protection, and simultaneously dripping a mixed solution 1 and a mixed solution 2 into the reactor, wherein the mixed solution 1 is prepared by mixing 40-50 parts of acrylic acid, 20-30 parts of maleic anhydride, 5-6 parts of sodium methacrylic sulfonate, 2-3 parts of mercaptopropionic acid and 80-100 parts of water, and the mixed solution 2 is prepared by mixing 1.5-2 parts of ammonium persulfate and 30 parts of water; the dripping time is 3-4 hours, and after the dripping is completed, the constant temperature stirring is continued for 5-6 hours, and then the temperature is lowered to below 50° C., and the pH value is adjusted to 7-7.5 with sodium hydroxide solution; and then the polycarboxylate water-reducing agent is obtained after purification by dialysis.
[0016] Preferably, the number average molecular weight of the isobutylene alcohol polyoxyethylene ether is 2000-3000, and the number average molecular weight of the methpropylene polyethylene glycol ether is 1500-2000.
[0017] Preferably, in step (1), the ratio of the total molar amount of calcium salt added to the reactor to the total molar amount of silicon salt added is 1.1-1.5:1; and the mass ratio of the polycarboxylate water reducer / lanthanum nitrate / cerium nitrate aqueous solution to the calcium salt aqueous solution is 1:0.3-0.5.
[0018] Preferably, in step (1), the calcium salt aqueous solution is one of a calcium nitrate aqueous solution and a calcium chloride aqueous solution; the silicon salt aqueous solution is one of a sodium silicate aqueous solution and a potassium silicate aqueous solution; the mass fraction of the calcium salt aqueous solution is 5-10%, and the mass fraction of the silicon salt aqueous solution is 8-15%.
[0019] Preferably, in step (2), the mass fraction of the p-phenylenediamine aqueous solution is 3-4%, the mass fraction of the ammonium persulfate aqueous solution is 0.5-1%, and the molar ratio of p-phenylenediamine and ammonium persulfate added dropwise to the reaction kettle is 1:0.5-0.7;
[0020] The molar ratio of the p-phenylenediamine added dropwise to the reaction kettle in step (2) to the silicon salt added dropwise to the reaction kettle in step (1) is 0.08-0.15:1.
[0021] Preferably, in step (1), the time for adding the calcium salt aqueous solution and the silicon salt aqueous solution to the reaction kettle is 5-9 hours; the time for continuing to stir the reaction is 150-180 minutes;
[0022] In step (2), the stirring reaction is continued for 30-60 minutes; during the centrifugal washing, water and ethanol are used for washing in sequence.
[0023] As a general inventive concept, the present invention also provides a nano calcium silicate hydrate type super early strength agent, which is prepared by the preparation method of the nano calcium silicate hydrate type super early strength agent.
[0024] As a general inventive concept, the present invention also provides an application of a nano calcium silicate hydrate type super early strength agent, specifically applying the nano calcium silicate hydrate type super early strength agent to the preparation of concrete, the raw materials for preparing the concrete include a gel material, and the amount of the nano calcium silicate hydrate type super early strength agent added to the concrete is 0.7-1.8% of the mass of the gel material.
[0025] The beneficial effects of the present invention are:
[0026] 1. The present invention in-situ polymerizes poly(p-phenylenediamine) on the calcium silicate hydrate prepared in step (1). The poly(p-phenylenediamine) is adsorbed on the surface of the calcium silicate hydrate with strong adsorption force and intercalated into the interlayer of the nano-CSH calcium silicate hydrate. Due to the presence of the benzene ring, a strong electrostatic repulsion and a greater steric hindrance can be generated, which effectively prevents the agglomeration of the nano-calcium silicate hydrate particles, and can make the nano-calcium silicate hydrate maintain a higher and more stable dispersibility. The particle size of the nano-calcium silicate hydrate is further reduced, and the specific surface area is increased, so that when the nano-calcium silicate hydrate type super early strength agent is used to prepare concrete, a uniform and compact structure can be formed in the early stage of cement hydration.
[0027] 2. In the preparation of the nano calcium silicate hydrate type super early strength agent of the present invention, lanthanum nitrate and cerium nitrate are added to the polycarboxylate water-reducing agent solution. Through the combination of the above rare earth compounds, the formed nano calcium silicate hydrate can have a smaller particle size, so that when preparing concrete, more nucleation sites can be formed to facilitate the nucleation growth of CSH gel.
[0028] 3. The polycarboxylate water-reducing agent prepared by the method of the present invention can be effectively adsorbed on the surface of nano calcium silicate hydrate and intercalated on the surface of nano calcium silicate hydrate, has a strong steric hindrance, and can make the size of the prepared nano calcium silicate hydrate crystal nucleus small.
[0029] 4. The average particle size of the nano calcium silicate hydrate type super early strength agent prepared by the method of the present invention is between 60-110nm, and the dispersibility is strong. When used in the preparation of concrete, it can effectively reduce the nucleation barrier of the hydration product CSH gel, form more nucleation sites, accelerate the cement hydration rate, and effectively improve the early strength of concrete. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] The present invention prepares a nano calcium silicate hydrate type super early strength agent, and the polycarboxylate water reducer prepared by the method of the present invention. The preparation method of the polycarboxylate water reducer is as follows:
[0032] ① Preparation of polycarboxylic acid water reducer Ⅰ.
[0033] The preparation method of polycarboxylate water reducer I comprises the following steps: adding 180 parts of isobutylene alcohol polyoxyethylene ether (number average molecular weight is 2500), 25 parts of methacrylic polyglycol ether (number average molecular weight is 1800) and 170 parts of water into a reactor, stirring and heating to 80°C under nitrogen protection, and then dripping mixed solution 1 and mixed solution 2 into the reactor at the same time, wherein the mixed solution 1 is prepared by mixing 45 parts of acrylic acid, 30 parts of maleic anhydride, 6 parts of sodium methacrylic sulfonate, 2.5 parts of mercaptopropionic acid and 90 parts of water, and the mixed solution 2 is prepared by mixing 2 parts of ammonium persulfate and 30 parts of water; the dripping time is 4 hours, and after the dripping is completed, the stirring is continued at a constant temperature for 5.5 hours, and then the temperature is lowered to below 50°C, and the pH value is adjusted to 7-7.5 with sodium hydroxide solution; and then the polycarboxylate water reducer I is obtained after purification by dialysis.
[0034] ② Preparation of polycarboxylic acid water reducer II.
[0035] The preparation method of polycarboxylate water reducer II comprises the following steps: adding 160-180 parts of isobutylene alcohol polyoxyethylene ether (number average molecular weight is 2500), 20 parts of methacrylic polyglycol ether (number average molecular weight is 1800) and 155 parts of water into a reactor, stirring and heating to 80°C under nitrogen protection, and simultaneously dripping mixed solution 1 and mixed solution 2 into the reactor, wherein the mixed solution 1 is prepared by mixing 40 parts of acrylic acid, 25 parts of maleic anhydride, 5 parts of sodium methacrylic sulfonate, 2 parts of mercaptopropionic acid and 80 parts of water, and the mixed solution 2 is prepared by mixing 1.5 parts of ammonium persulfate and 30 parts of water; the dripping time is 4 hours, and after the dripping is completed, the constant temperature stirring is continued for 6 hours, and then the temperature is lowered to below 50°C, and the pH value is adjusted to 7-7.5 with sodium hydroxide solution; and then the polycarboxylate water reducer II is obtained after purification by dialysis.
[0036] ③ Preparation of polycarboxylic acid water reducer III.
[0037] The preparation method of polycarboxylate water reducer III comprises the following steps: adding 160-180 parts of isobutylene alcohol polyoxyethylene ether (number average molecular weight is 2500), 15 parts of methacrylic polyglycol ether (number average molecular weight is 1800) and 150 parts of water into a reactor, stirring and heating to 85°C under nitrogen protection, and simultaneously dripping mixed solution 1 and mixed solution 2 into the reactor, wherein the mixed solution 1 is prepared by mixing 50 parts of acrylic acid, 20 parts of maleic anhydride, 6 parts of sodium methacrylic sulfonate, 3 parts of mercaptopropionic acid and 100 parts of water, and the mixed solution 2 is prepared by mixing 2 parts of ammonium persulfate and 30 parts of water; the dripping time is 3 hours, and after the dripping is completed, the constant temperature stirring is continued for 5 hours, and then the temperature is lowered to below 50°C, and the pH value is adjusted to 7-7.5 with sodium hydroxide solution; and then the polycarboxylate water reducer III is obtained after purification by dialysis.
[0038] Embodiment 1:
[0039] A method for preparing a nano calcium silicate hydrate type super early strength agent comprises the following steps:
[0040] (1) Add polycarboxylate water-reducing agent II / lanthanum nitrate / cerium nitrate aqueous solution to a reactor, wherein the mass fraction of polycarboxylate water-reducing agent II is 5%, the mass fraction of lanthanum nitrate is 0.2%, and the mass fraction of cerium nitrate is 0.1%; and add sodium hydroxide solution to adjust the pH value to 12, raise the temperature to 55°C, and then, under nitrogen protection, add 8% calcium nitrate aqueous solution and 13% sodium silicate aqueous solution dropwise to the reactor while stirring, and the dropwise addition time is 8 hours; after the dropwise addition is completed, add sodium hydroxide solution to adjust the pH value to 12.5, close the reactor and raise the temperature to 80°C, and continue to stir and react at constant temperature for 180 minutes.
[0041] In the above steps, the ratio of the total molar amount of calcium nitrate added to the reactor to the total molar amount of sodium silicate added is 1.3: 1. The mass ratio of the polycarboxylate water reducer II / lanthanum nitrate / cerium nitrate aqueous solution to the calcium nitrate aqueous solution is 1:0.3.
[0042] (2) Then the temperature is lowered to 50°C, a dilute nitric acid solution is added to adjust the pH value to 7.5, and under nitrogen protection, a 4% by mass aqueous solution of p-phenylenediamine and a 0.8% by mass aqueous solution of ammonium persulfate are added dropwise to the reactor while stirring. After the addition is completed, the reaction is continued at a constant temperature and stirred for 50 minutes, and then cooled to room temperature, centrifuged and washed (washed with water and ethanol in turn), and freeze-dried to obtain a nano-hydrated calcium silicate type super early strength agent.
[0043] In the above step (2), the molar ratio of p-phenylenediamine and ammonium persulfate added to the reactor is 1:0.5; and the molar ratio of p-phenylenediamine added to the reactor in step (2) to sodium silicate added to the reactor in step (1) is 0.12:1.
[0044] Embodiment 2:
[0045] A method for preparing a nano calcium silicate hydrate type super early strength agent comprises the following steps:
[0046] (1) Add polycarboxylate water-reducing agent I / lanthanum nitrate / cerium nitrate aqueous solution to a reactor, wherein the mass fraction of polycarboxylate water-reducing agent I is 4%, the mass fraction of lanthanum nitrate is 0.2%, and the mass fraction of cerium nitrate is 0.15%; and add sodium hydroxide solution to adjust the pH value to 11.5, raise the temperature to 50°C, and then, under nitrogen protection, add 5% calcium nitrate aqueous solution and 8% potassium silicate aqueous solution dropwise to the reactor while stirring, and the dropping time is 5 hours; after the dropwise addition is completed, add sodium hydroxide solution to adjust the pH value to 12, close the reactor and raise the temperature to 80°C, and continue to stir and react at constant temperature for 160 minutes.
[0047] In the above steps, the ratio of the total molar amount of calcium nitrate added to the reactor to the total molar amount of potassium silicate added is 1.2: 1. The mass ratio of the polycarboxylate water reducer I / lanthanum nitrate / cerium nitrate aqueous solution to the calcium nitrate aqueous solution is 1:0.5.
[0048] (2) Then the temperature is lowered to 50°C, a dilute nitric acid solution is added to adjust the pH value to 7.5, and under nitrogen protection, a 3.5% by mass p-phenylenediamine aqueous solution and a 0.7% by mass ammonium persulfate aqueous solution are added dropwise to the reactor while stirring. After the addition is completed, the reaction is continued at a constant temperature and stirred for 50 minutes, and then cooled to room temperature, centrifuged and washed (washed with water and ethanol in turn), and freeze-dried to obtain a nano-hydrated calcium silicate type super early strength agent.
[0049] In the above step (2), the molar ratio of p-phenylenediamine and ammonium persulfate added to the reactor is 1:0.6; and the molar ratio of p-phenylenediamine added to the reactor in step (2) to potassium silicate added to the reactor in step (1) is 0.1:1.
[0050] Embodiment 3:
[0051] A method for preparing a nano calcium silicate hydrate type super early strength agent comprises the following steps:
[0052] (1) Add polycarboxylate water-reducing agent II / lanthanum nitrate / cerium nitrate aqueous solution to a reactor, wherein the mass fraction of polycarboxylate water-reducing agent II is 3%, the mass fraction of lanthanum nitrate is 0.2%, and the mass fraction of cerium nitrate is 0.15%; and add sodium hydroxide solution to adjust the pH value to 12, raise the temperature to 50°C, and then, under nitrogen protection, add 8% calcium nitrate aqueous solution and 11% sodium silicate aqueous solution dropwise to the reactor while stirring, and the dropwise addition time is 7 hours; after the dropwise addition is completed, add sodium hydroxide solution to adjust the pH value to 12.5, close the reactor and raise the temperature to 70°C, and continue to stir and react at constant temperature for 180 minutes.
[0053] In the above steps, the ratio of the total molar amount of calcium nitrate added to the reactor to the total molar amount of sodium silicate added is 1.1: 1. The mass ratio of the polycarboxylate water reducer II / lanthanum nitrate / cerium nitrate aqueous solution to the calcium nitrate aqueous solution is 1:0.4.
[0054] (2) Then the temperature is lowered to 50°C, a dilute nitric acid solution is added to adjust the pH value to 7.5, and under nitrogen protection, a 4% by mass aqueous solution of p-phenylenediamine and a 1% by mass aqueous solution of ammonium persulfate are added dropwise to the reactor while stirring. After the addition is completed, the reaction is continued at a constant temperature and stirred for 60 minutes, and then cooled to room temperature, centrifuged and washed (washed with water and ethanol in turn), and freeze-dried to obtain a nano-hydrated calcium silicate type super early strength agent.
[0055] In the above step (2), the molar ratio of p-phenylenediamine and ammonium persulfate added to the reactor is 1:0.55; and the molar ratio of p-phenylenediamine added to the reactor in step (2) to sodium silicate added to the reactor in step (1) is 0.12:1.
[0056] Embodiment 4:
[0057] A method for preparing a nano calcium silicate hydrate type super early strength agent comprises the following steps:
[0058] (1) Add polycarboxylate water-reducing agent III / lanthanum nitrate / cerium nitrate aqueous solution to a reactor, wherein the mass fraction of polycarboxylate water-reducing agent III is 5%, the mass fraction of lanthanum nitrate is 0.15%, and the mass fraction of cerium nitrate is 0.05%; and add sodium hydroxide solution to adjust the pH value to 11.5, raise the temperature to 55° C., and then, under nitrogen protection, add a 10% mass fraction of calcium chloride aqueous solution and a 15% mass fraction of sodium silicate aqueous solution to the reactor while stirring, and the addition time is 9 hours; after the addition is completed, add sodium hydroxide solution to adjust the pH value to 12.5, close the reactor and raise the temperature to 75° C., and continue to stir and react at constant temperature for 150 minutes.
[0059] In the above steps, the ratio of the total molar amount of calcium chloride added to the reactor to the total molar amount of sodium silicate added is 1.5: 1. The mass ratio of the polycarboxylate water reducer III / lanthanum nitrate / cerium nitrate aqueous solution to the calcium chloride aqueous solution is 1:0.35.
[0060] (2) Then the temperature is lowered to 40°C, a dilute nitric acid solution is added to adjust the pH value to 7, and under nitrogen protection, a 3.5% by mass p-phenylenediamine aqueous solution and a 0.5% by mass ammonium persulfate aqueous solution are added dropwise to the reactor while stirring. After the addition is completed, the reaction is continued at a constant temperature and stirred for 30 minutes, and then cooled to room temperature, centrifuged and washed (washed with water and ethanol in turn), and freeze-dried to obtain a nano-hydrated calcium silicate type super early strength agent.
[0061] In the above step (2), the molar ratio of p-phenylenediamine and ammonium persulfate added to the reactor is 1:0.5; and the molar ratio of p-phenylenediamine added to the reactor in step (2) to sodium silicate added to the reactor in step (1) is 0.08:1.
[0062] Embodiment 5:
[0063] A method for preparing a nano calcium silicate hydrate type super early strength agent comprises the following steps:
[0064] (1) Add polycarboxylate water-reducing agent I / lanthanum nitrate / cerium nitrate aqueous solution to a reactor, wherein the mass fraction of polycarboxylate water-reducing agent I is 6%, the mass fraction of lanthanum nitrate is 0.15%, and the mass fraction of cerium nitrate is 0.1%; and add sodium hydroxide solution to adjust the pH value to 11.5, raise the temperature to 55°C, and then, under nitrogen protection, add a 5% calcium nitrate aqueous solution and an 8% sodium silicate aqueous solution dropwise to the reactor while stirring, and the dropwise addition time is 6 hours; after the dropwise addition is completed, add sodium hydroxide solution to adjust the pH value to 12, close the reactor and raise the temperature to 80°C, and continue to stir and react at constant temperature for 170 minutes.
[0065] In the above steps, the ratio of the total molar amount of calcium nitrate added to the reactor to the total molar amount of sodium silicate added is 1.3: 1. The mass ratio of the polycarboxylate water reducer I / lanthanum nitrate / cerium nitrate aqueous solution to the calcium nitrate aqueous solution is 1:0.5.
[0066] (2) Then the temperature is lowered to 50°C, a dilute nitric acid solution is added to adjust the pH value to 7.5, and under nitrogen protection, a 3% by mass p-phenylenediamine aqueous solution and a 0.8% by mass ammonium persulfate aqueous solution are added dropwise to the reactor while stirring. After the addition is completed, the reaction is continued at a constant temperature and stirred for 50 minutes, and then cooled to room temperature, centrifuged and washed (washed with water and ethanol in turn), and freeze-dried to obtain a nano-hydrated calcium silicate type super early strength agent.
[0067] In the above step (2), the molar ratio of p-phenylenediamine and ammonium persulfate added to the reactor is 1:0.7; and the molar ratio of p-phenylenediamine added to the reactor in step (2) to sodium silicate added to the reactor in step (1) is 0.15:1.
[0068] Comparative Example 1:
[0069] A method for preparing a nano calcium silicate hydrate type super early strength agent comprises the following steps:
[0070] Add polycarboxylate water reducer II / lanthanum nitrate / cerium nitrate aqueous solution to the reactor, wherein the mass fraction of polycarboxylate water reducer II is 5%, the mass fraction of lanthanum nitrate is 0.2%, and the mass fraction of cerium nitrate is 0.1%; and add sodium hydroxide solution to adjust the pH value to 12, heat it to 55°C, and then, under nitrogen protection, add 8% calcium nitrate aqueous solution and 13% sodium silicate aqueous solution to the reactor while stirring, and the dropwise addition time is 8h; after the dropwise addition is completed, add sodium hydroxide solution to adjust the pH value to 12.5, close the reactor and heat it to 80°C, continue to stir and react at constant temperature for 180min. Then cool to room temperature, centrifuge and wash, and freeze-dry to obtain nano-hydrated calcium silicate type super early strength agent.
[0071] In the above steps, the ratio of the total molar amount of calcium nitrate added to the reactor to the total molar amount of sodium silicate added is 1.3: 1. The mass ratio of the polycarboxylate water reducer II / lanthanum nitrate / cerium nitrate aqueous solution to the calcium nitrate aqueous solution is 1:0.3.
[0072] Comparative Example 2:
[0073] A method for preparing a nano calcium silicate hydrate type super early strength agent comprises the following steps:
[0074] (1) Add polycarboxylate water-reducing agent II aqueous solution to a reactor, wherein the mass fraction of polycarboxylate water-reducing agent II is 5%; and add sodium hydroxide solution to adjust the pH value to 12, raise the temperature to 55°C, and then, under nitrogen protection, add 8% calcium nitrate aqueous solution and 13% sodium silicate aqueous solution to the reactor while stirring, and the addition time is 8 hours; after the addition is completed, add sodium hydroxide solution to adjust the pH value to 12.5, close the reactor and raise the temperature to 80°C, and continue to stir and react at constant temperature for 180 minutes.
[0075] In the above steps, the ratio of the total molar amount of calcium nitrate added to the reactor to the total molar amount of sodium silicate added is 1.3: 1. The mass ratio of the polycarboxylate water-reducing agent II aqueous solution to the calcium nitrate aqueous solution is 1:0.3.
[0076] (2) Then the temperature is lowered to 50°C, a dilute nitric acid solution is added to adjust the pH value to 7.5, and under nitrogen protection, a 4% by mass aqueous solution of p-phenylenediamine and a 0.8% by mass aqueous solution of ammonium persulfate are added dropwise to the reactor while stirring. After the addition is completed, the reaction is continued at a constant temperature and stirred for 50 minutes, and then cooled to room temperature, centrifuged and washed (washed with water and ethanol in turn), and freeze-dried to obtain a nano-hydrated calcium silicate type super early strength agent.
[0077] In the above step (2), the molar ratio of p-phenylenediamine and ammonium persulfate added to the reactor is 1:0.5; and the molar ratio of p-phenylenediamine added to the reactor in step (2) to sodium silicate added to the reactor in step (1) is 0.12:1.
[0078] Performance Test:
[0079] Concrete was prepared by using the nano calcium silicate hydrate type super early strength agent in Examples 1-5 and Comparative Examples 1-2 to obtain concrete 1-7, which all included the following raw materials in parts by weight: 500 parts of P.O52.5 grade ordinary Portland cement, 1200 parts of crushed stone (particle size 5-20 mm), 1000 parts of river sand (fineness modulus 2.6), 6 parts of polycarboxylate water reducer (water reducer I in the present invention), 6 parts of nano calcium silicate hydrate type super early strength agent, and 190 parts of water. Then, the above groups of concrete were subjected to compressive strength test and setting time test.
[0080] The compressive strength test of concrete was carried out in accordance with GB / T 50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete". The concrete molding size was 150mm×150mm×150mm and was placed in a standard curing room for curing. The specific test results are shown in Table 1.
[0081] Table 1 Concrete compressive strength test results
[0082]
[0083]
[0084] The setting time test of concrete was carried out in accordance with GB / T 50080-2016 “Standard for test methods for properties of ordinary concrete mixtures”. The specific test results are shown in Table 2.
[0085] Table 2 Concrete setting time test results
[0086] Super early strength agent Initial setting time Final setting time Concrete 1 Example 1 3h20min 6h Concrete 2 Example 2 3h 5h40min Concrete 3 Example 3 3h40min 6h30min Concrete 4 Example 4 3h30min 6h30min Concrete 5 Example 5 3h20min 5h50min Concrete 6 Comparative Example 1 4h40min 7h30min Concrete 7 Comparative Example 2 4h20min 7h
[0087] It can be seen from Table 1 and Table 2 that the use of the nano calcium silicate hydrate type super early strength agent of the present invention to prepare concrete can make the obtained concrete have higher early strength and shorter setting time. And from the comparison between concrete 1 and concrete 6-7, it can be seen that when preparing the nano calcium silicate hydrate type super early strength agent, by adding lanthanum nitrate and cerium nitrate to the polycarboxylate water-reducing agent solution, and by in-situ polymerizing poly-p-phenylenediamine on the calcium silicate hydrate prepared in step (1), the early strength of the concrete can be improved and the setting time of the concrete can be shortened.
[0088] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a nano calcium silicate hydrate type super early strength agent, characterized in that: The following steps are involved: (1) adding a polycarboxylate water-reducing agent / lanthanum nitrate / cerium nitrate aqueous solution to a reactor, and adding a sodium hydroxide solution to adjust the pH value to 11.5-12, heating to 50-55° C., and then dripping a calcium salt aqueous solution and a silicon salt aqueous solution into the reactor while stirring under nitrogen protection, after the dripping is completed, adding a sodium hydroxide solution to adjust the pH value to 12-12.5, closing the reactor and heating to 70-80° C., and continuing to stir the reaction at a constant temperature; In the polycarboxylate water-reducing agent / lanthanum nitrate / cerium nitrate aqueous solution, the mass fraction of the polycarboxylate water-reducing agent is 3-6%, the mass fraction of the lanthanum nitrate is 0.1-0.2%, and the mass fraction of the cerium nitrate is 0.05-0.15%; The ratio of the total molar amount of the calcium salt added to the reactor to the total molar amount of the silicon salt added is 1.1-1.5:1; the calcium salt aqueous solution is one of a calcium nitrate aqueous solution and a calcium chloride aqueous solution; the silicon salt aqueous solution is one of a sodium silicate aqueous solution and a potassium silicate aqueous solution; the mass fraction of the calcium salt aqueous solution is 5-10%, and the mass fraction of the silicon salt aqueous solution is 8-15%; The preparation method of the polycarboxylate water-reducing agent comprises the following steps: adding 160-180 parts of isobutylene alcohol polyoxyethylene ether, 15-25 parts of methacrylic polyglycol ether and 150-170 parts of water into a reactor, stirring and heating to 80-85° C. under nitrogen protection, and simultaneously dropping a mixed solution 1 and a mixed solution 2 into the reactor, wherein the mixed solution 1 is prepared by mixing 40-50 parts of acrylic acid, 20-30 parts of maleic anhydride, 5-6 parts of sodium methacrylic sulfonate, 2-3 parts of mercaptopropionic acid and 80-100 parts of water, and the mixed solution 2 is prepared by mixing 1.5-2 parts of ammonium persulfate and 30 parts of water; the dropping time is 3-4 hours, and after the dropping is completed, the stirring is continued at a constant temperature for 5-6 hours, and then the temperature is lowered to below 50° C., and the pH value is adjusted to 7-7.5 with a sodium hydroxide solution; and then the polycarboxylate water-reducing agent is obtained after purification by dialysis; The number average molecular weight of the isobutylene alcohol polyoxyethylene ether is 2000-3000, and the number average molecular weight of the methacrylic polyethylene glycol ether is 1500-2000; (2) then cooling to 40-50° C., adding dilute nitric acid solution to adjust the pH value to 7-7.5, and under nitrogen protection, adding p-phenylenediamine aqueous solution and ammonium persulfate aqueous solution to the reaction kettle while stirring. After the addition is complete, continue to stir the reaction at a constant temperature, then cool to room temperature, centrifuge and wash, and freeze-dry to obtain the nano-hydrated calcium silicate type super early strength agent; The mass fraction of the p-phenylenediamine aqueous solution is 3-4%, the mass fraction of the ammonium persulfate aqueous solution is 0.5-1%, and the molar ratio of the p-phenylenediamine and ammonium persulfate added dropwise to the reaction kettle is 1:0.5-0.7; The molar ratio of the p-phenylenediamine added dropwise to the reaction kettle in step (2) to the silicon salt added dropwise to the reaction kettle in step (1) is 0.08-0.15:
1.
2. The method for preparing the nano calcium silicate hydrate type super early strength agent according to claim 1, characterized in that: In step (1), the time for adding the calcium salt aqueous solution and the silicon salt aqueous solution to the reaction kettle is 5-9 hours; the time for continuing to stir the reaction is 150-180 minutes; In step (2), the stirring reaction is continued for 30-60 minutes; during the centrifugal washing, water and ethanol are used for washing in sequence.
3. A nano calcium silicate hydrate type super early strength agent, characterized in that: The nano calcium silicate hydrate super early strength agent is prepared by the preparation method according to any one of claims 1 to 2.
4. An application of the nano calcium silicate hydrate type super early strength agent as claimed in claim 3, characterized in that: The nano calcium silicate hydrate type super early strength agent is used in preparing concrete. The raw materials for preparing the concrete include gel material. The amount of the nano calcium silicate hydrate type super early strength agent added to the concrete is 0.7-1.8% of the mass of the gel material.
Citation Information
Patent Citations
Slow release slump retaining polycarboxylate water reducer and preparation thereof
CN102515618A
Alcohol amine modified hydrated calcium silicate nanocrystal nucleus early strength agent and preparation method thereof
CN111253107A